Diagnosis of a multifocal B cell lymphoma with preceding demyelinating central nervous system lesions by single voxel proton MR spectroscopy. Issue 2 (1st February 2001) - Kuhlmann, T; Schröter, A; Dechent, P; Weber, F; Rustenbeck, H H; Füzesi, L; Brück, W; Ehrenreich, H; Frahm, J
Abstract : Single voxel proton magnetic resonance spectroscopy (MRS) provides a rapid non-invasive fingerprint of tissue chemistry. A case history is presented in which a B cell lymphoma with antecedent demyelinating lesions of the CNS was suspected by MRS and confirmed by neuropathological examination and immunoglobulin gene rearrangement.